PEMANFAATAN MUSEUM UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR SEJARAH SISWA KELAS X SMK NEGERI 1 KASIHAN - Sumi Harti; Darsono (Universitas PGRI Yogyakarta, 2023)
This study aims to find out : 1) the use of museums as learning resources, 2) the use of museums in increasing interest in learnig history. 3) the use of museums to increase achievement in learning history. The method used in this research is a qualitative research method. Data collecttion techniques in this study are by observing, document studies, and interviews. The data analysis techniques used in this study are data collection, data reduction, data presentation, as well as verivication and drawing conclusions. The data validity checking technique used is technical triangulation and source triangulation. The result of this study that : 1) by visiting the museum the existing collections can be utilized by students from learning resources by utilizing museums student become very activate because studets can deeper knowledge about history so that various information that is in accordance with the material being taught can be obtained from museum visits, 2) by visiting museums or with virtual museums students can find out collection or historical object so that learning will be very enjoyable besides making students enthusiastic, the impact will certainly arouse student learning interest, 3) visiting museums can improve student achievement, this can be seen from the results of student tests before and after learning visiting museums or virtual museums, there is learning in a museum that can increase student interest in learning, student achievement will also increase based on test result data.